An Evaluation of The Compilation of a Country-Specific Mandarin Textbook: Tourism and Hotel Management for Special Purposes: 国别化“华语课本：旅游和酒店管理科专用”编写评析 - Low Hiang Loon (Mandarinable: Journal of Chinese Studies, 2024)
Driven by the “One Belt One Road Initiative”, Malaysia has a huge Chinese tourist market. In cultivating non-native Chinese to provide tourism and hotel services for Chinese tourists, does Malaysian country-specific "Mandarin Textbook: Tourism and Hotel Management for Special Purposes" meet the writing principle of Mandarin as a foreign language? This article evaluates and analyzes this teaching material based on three major principles, namely pertinence, practicality and scientificity. This article basically uses literature research method and comparative method to explore the global country-specific tourism Mandarin textbooks and related research, and compares and discusses with the Malaysian Mandarin Textbook. The findings show that this teaching material demonstrates its practicality: (1) It brings out the phenomenon of multi-racial and multi-cultural Malaysia; (2) It highlights the characteristics of tourist attractions in West and East Malaysia; (3) It shows the unique culture of Malaysia. However, the pertinence of this textbook has shortcomings. Although this textbook includes the role of local tour guide, the text repeatedly arranges the tour guide to travel as a tourist. In addition, the scientificity of this textbook needs to be strengthened. The compilation of the textbooks was mainly based on the writers’ years of teaching experience and reference to China's tourism Chinese textbooks. This article recommends that future textbooks need to be compiled based on learner needs analysis to improve the scientificity of the textbooks. Relevant content and vocabulary should be selected based on related corpora or published vocabulary lists to enhance the practicality of the teaching materials.